Metamodernism: A Response About Magic - Brand, Mattias (Method & theory in the study of religion, 2025)
Since Metamodernism presents a vision for the future of theory, one can expect to find fundamental insights to inspire empirical and historical research as well as crucial questions to discuss with graduate students. In this short response, I summarize some of the key terminology of Josephson Storm’s Metamodernism and attempt to apply it to the study of ancient magic. Despite the ambitious aims and density of the book, I would like to connect its theoretical questions concerning realism, ontology, semiotics, and the role of academic values to the day-to-day activities of my scholarship: historical research and teaching within the study of religion\s.